Recent progress in the synthesis of C-4′-spironucleosides and its future perspectives. Issue 22 (16th November 2020) - Kumar, Rajesh; Kumar, Manish; Kumar, Vijay; Kumar, Arbind; Haque, Navedul; Kumar, Ram; Prasad, Ashok K.
Abstract: Spironucleosides are a type of conformationally restricted bicycle nucleoside analogous in which the carbocyclic/heterocyclic ring is inserted at carbohydrate moiety of the nucleoside and this restrict the conformational flexibility of the carbohydrate ring. Hydantocidin is the first naturally occurring spironucleoside which shows potent herbicidal and plant growth regulatory activities. The biological activity of hydantocidin has encouraged the synthetic organic chemist to synthesize constrained nucleosides analogous for drug discovery. We present here an overview of the synthesis and biological importance of C -4′-spironucleoside analogous. Graphical Abstract: